Mode-Dependent Fracture Behavior of Asphalt Mixtures with Semicircular Bend Test. Issue 1 (January 2014) - Im, Soohyok; Ban, Hoki; Kim, Yong-Rak
Cracking in asphalt concrete pavements causes primary failure in the pavement structure. This cracking is considered one of the key issues to be addressed when paving materials are selected and sustainable pavement structures are designed. Given the diverse nature of traffic loads and pavement geometry, the asphalt mixture in the pavement is subjected to complex cracking behavior, such as mixed-mode fracture (i.e., the combination of an opening mode and a shearing mode of fracture). To date, most studies considered Mode 1 (opening) fractures only, because of technical challenges in testing and analysis. For a better understanding of asphalt fracture and more accurate design of pavement structure, mode-dependent fracture behavior needs to be characterized. This paper presents experimental efforts to characterize the mode-dependent fracture behavior of an asphalt mixture. Toward this end, semicircular bending (SCB) fracture tests were incorporated into the results of digital image correlation analysis for a fine aggregate matrix mixture subjected to a 10 mm/min loading rate and an intermediate temperature condition of 218C. To achieve different fracture modes (i.e., opening, sliding, and mixed), the geometric loading configurations of the SCB test were varied through the use of different initial notch inclination angles and different supporting spans. Test results were further analyzed to calculate fracture resistance. Observations from this study, though limited, imply that mixed-mode fracture characteristics exist and need to be considered in the structural design of asphalt pavements with which multiaxial cracking usually is associated.